RESTRUKTURISASI STATUS RUMAH SAKIT UMUM DAERAH PADANGAN BOJONEGORO DARI SATUAN KERJA PERANGKAT DAERAH MENJADI BADAN LAYANAN UMUM DAERAH - Apriliyanto, Dimas Rahardiyan (Jurnal Ilmiah Mahasiswa FEB, 2016)
This Research  aims  to know  the restructuring process Padangan General Hospital from Regional Work Unit  to Public Service Agency, various constraints faced by Padangan General Hospital as well as the  solution to overcome those obstacles, and various advantages or disadvantages received by the patients or the hospital when it becomes Public Service Agency. The type of this research is case study  research with quantitative descriptive approach. Data used in this research are both  quantitative data and qualitative data. The data  source was attained through  interview and various documents directly from Padangan  General Hospital. Data analysis in this research is done through measuring  the feasibility of Padangan  General  Hospital  to be  Public Service Agency by using two indicators  such as service indicators  provided to the public and financial performance  indicators  of Padangan  General  Hospital  based on  Cost Recovery Rate Method.  The researchers also analyzed the  transformation  process  of Padangan General Hospital from Regional Work Unit to Public Service Agency by comparing the procedures based on Law No. 23 in  2005 about Financial Management of Public Service Agency  to  the existing reality. Based on  the conducted data analysis, it concludes that Padangan General Hospital is feasible to be upgraded  to Public Service Agency; further, the result of  restructuring processes taken by Padangan General Hospital demonstrate some changes on organizational structure, employee recruitment and selection processes, asset management and procurement processes, as well as financial management.  By becoming Public Service Agency, it is expected that Padangan General Hospital can improve  its service  performance provided to  the population and able to be more self-dependent in financing its entire operation.   Keywords: Restructuring, Public Service Agency, Padangan Hospital,  Financial Performance, Service Performance, Constraints, Advantage